(untitled) (International Congress on Economics, Management and Business Studies, 2026)
This research paper details the current need for a complete digitalization of the tax system, including the integration of artificial intelligence systems, which will simplify accounting for taxpayers, including large enterprises and clusters, and reduce the workload of civil servants.